Iron Acquisition Mechanisms and Their Role in the Virulence of Burkholderia Species - Butt, Aaron T.; Thomas, Mark S. (Frontiers in Cellular and Infection Microbiology, 2017)
Burkholderia is a genus within the β-Proteobacteriaceae that contains at least 90 validly named species which can be found in a diverse range of environments. A number of pathogenic species occur within the genus. These include B. cenocepacia and B. multivorans, opportunistic pathogens that can infect the lungs of patients with cystic fibrosis, and are members of the Burkholderia cepacia complex (Bcc). B. pseudomallei, is also an opportunistic pathogen, but in contrast to Bcc species it causes the tropical human disease melioidosis, while its close relative B. mallei is the causative agent of glanders in horses. For these pathogens to survive within a host and cause disease they must be able to acquire iron. This chemical element is essential for nearly all living organisms due to its important role in many enzymes and metabolic processes. In the mammalian host, the amount of accessible free iron is negligible due to the low solubility of the metal ion in its higher oxidation state and the tight binding of this element by host proteins such as ferritin and lactoferrin. As with other pathogenic bacteria, Burkholderia species have evolved an array of iron acquisition mechanisms with which to capture iron from the host environment. These mechanisms include the production and utilisation of siderophores and the possession of a haem uptake system. Here, we summarise the known mechanisms of iron acquisition of pathogenic Burkholderia species and discuss the evidence for their importance in the context of virulence and the establishment of infection in the host. We have also carried out an extensive bioinformatic analysis to identify which siderophores are produced by each Burkholderia species that is pathogenic to humans.